Uang Dan Moneter Dalam Sistem Keuangan Islam - Joko Hadi Purnomo; Moh. Agus Sifa' (JOURNAL OF SHARIA ECONOMICS, 2019)
Money is a tool that can be used in conducting exchanges or transactions both goods and services in a certain area. Money is the standard of use found in goods and labor. Therefore, money is defined as a tool to measure the value of each item and service. There are two main policies in the economy called fiscal and monetary policies. Monetary policy is a policy that is carried out to control the supply and demand of money (money circulating in the community), the available money supply, the stability of the currency's value and the direction in which money will be allocated using appropriate monetary tools or instruments in order to achieve the objectives from monetary policy itself. The fiscal policy is a policy that is used to move the steps to obtain state income including tax revenue and control the direction of fiscal policy and control the amount of government spending and expenditure using fiscal tools, so that the objectives of the policy can be achieved fiscal itself in the economy. In this study, the author only focuses on discussing monetary policy and its implications for economic development in an Islamic perspective. Keywords: money, monetary, Islamic finance system